Calcium isotope systematics at hydrothermal conditions: Mid-ocean ridge vent fluids and experiments in the CaSO4-NaCl-H2O system. (1st April 2018) - Scheuermann, Peter P.; Syverson, Drew D.; Higgins, John A.; Pester, Nicholas J.; Seyfried, William E.
Abstract: Two sets of hydrothermal experiments were performed to explore Ca isotope fractionation and exchange rates at hydrothermal conditions (410–450 °C, 31.0–50.0 MPa). The first set of experiments determined the magnitude of vapor-liquid Ca isotope fractionation and anhydrite solubility in the CaSO4 -NaCl-H2 O system. The data indicate no statistical difference between the Ca isotopic composition of coexisting vapor and liquid. The second set of experiments utilized an anomalous 43 Ca spike to determine the rate of Ca exchange between fluid and anhydrite as a function of total dissolved Ca concentration. Results show that the rate of exchange increases with dissolved Ca concentrations (12–23 mM/kg), but no change in exchange rate is observed when the Ca concentration increases from 23 to 44 mM/kg Ca. 74–142 days are required to achieve 90% anhydrite-fluid Ca isotope exchange at the conditions investigated, while only several hours are necessary for vapor-liquid isotopic equilibrium. The lack of vapor-liquid Ca isotope fractionation in our experiments is consistent with δ 44 Ca of mid-ocean ridge hydrothermal vent fluids that remain constant, regardless of chlorinity. Moreover, the narrow range of end member fluid δ 44 Ca, −0.98 to −1.13‰ (SW), is largely indistinguishable from MORB δ 44 Ca, suggesting that neither phase separation nor fluid-rock interactions at depth significantly fractionate Ca isotopes in modern high-temperature mid-ocean ridge hydrothermal systems.